PENGGUNAAN EMBUNG GEOMEMBRANE SEBAGAI PENAMPUNGAN AIR BERSIH DESA TANGGUNG PRIGEL - Mukhammad Alifuddin; Sugeng Dwi Hartantyo (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2018)
The technology of artificial geomembrane reservoir or water tank is the small reservoir in the village land (TKD) which is built to collect the water in the rainy season by using waterproof material as the layer by utilizing the rainwater through the river around which is then used as an alternative source of clean water (water supply) in the dry season. As for the calculation methods used for this research include: analysis of rainfall area using algebra average method (arithematic mean), the calculation of rainfall plan can be done by using disperse measurement, with the statistical parameter of calculation result of Sd= 23.884 Cs= 1.933 Ck= 4.031 Cv= 0.233. The distribution analysis is done using Gumbel 1 method for 10 years plan amounted to 146.601 mm/day. Rainfall intensity analysis is done by using Mononobe method for 10 years rainfall intensity plan amounted to 6.108 mm/hour. For the next 10 years population projection is done using calculation of Arithmetic method of 2.795 populations. The conclusion of this research indicates that the clean water need in the dry season at Tanggung Prigel Village, Glagah District in 2026 is approximately 0.001941 m3/sec. While the plan for reservoir debit of 0.003254 m3/sec so it is considered sufficient to fulfill the clean water need in the Tanggung Prigel Village, Glagah District.